Boundaries and continuities: a genealogical approach to some illness representations in Finland - Marja-Liisa Honkasalo; Reea Hinkkanen (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Boundaries and continuities: a genealogical approach to some illness representations in Finland